Waste Biomass Valorisation for the Development of Sustainable Cellulosic Aerogels and their Sound Absorption Properties. (30th August 2022) - Benito‐González, Isaac; Cucharero, Jose; Al Haj, Yazan; Hänninen, Tuomas; Lokki, Tapio; Martínez‐Sanz, Marta; López‐Rubio, Amparo; Martínez‐Abad, Antonio; Vapaavuori, Jaana
Abstract: Novel and more sustainable sound absorbing materials are produced through the valorization of waste biomass sources by following circular economy principles. Cellulosic nanocrystals (CNC) were extracted from Posidonia oceanica dead leaves, spent barely grains, and kale stems using a simplified purification protocol. These nanocrystals are used to prepare cellulosic aerogels, evaluating the effect of three parameters, namely, concentration (0.5–4%), CaCl2 and poly(lactic acid) (PLA) incorporation (hybrid aerogels), on their sound absorption properties. Aerogels from 4% suspensions show the highest sound absorption, outperforming benchmark rockwool and polyester—two modern commonly‐used sound absorbers. Moreover, PLA coating also improves the sound absorption performance of the most aerogels. CNC from KS aerogels are selected as the optimum at both high (500–6000 Hz) and low (100–1500 Hz) frequency ranges. Overall, these results represent a new proof‐of‐concept of waste biomass conversion to high‐performance cellulosic aerogels that have excellent sound absorbing properties. Abstract : A sustainable proof‐of‐concept route from three different waste biomasses to high performance sound absorption materials is demonstrated. In addition to exceeding the performance of commercial standard references, these materials have a key advantage of low density, thus opening up new possibilities for light‐weight acoustic absorbents.